2020
DOI: 10.20944/preprints202005.0499.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding the Spread of COVID-19 in Japan: Preliminary Results from a System Dynamics Model

Abstract: This study developed a system dynamics model to understand the spread of coronavirus disease (COVID-19) in Japan. The model is built on the generic SEIR (Susceptible, Exposed, Infected, and Recovered) framework adopted by Ghaffarzadegan and Rahmandad (2020) to build a system dynamics model for the spread of COVID-19 in Iran. Japan seems to be successful in containing the spread compared with other countries, and its first peak has passed. However, because this also leaves a large population still susceptible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…As an example, the COVID-19 pandemic dynamics in Japan in the summer of 2020, 2021 and 2022 will be investigated in order to estimate the impact of vaccination levels on the numbers of new infections, death, and mortality rates. Some other studies of COVID-19 dynamics in Japan can be found in ( Chen et al., 2021 ; Fukumoto et al., 2021 ; Nesteruk, 2022a ; Nesteruk, 2022b ; Nesteruk, 2022c ; Niwa et al., 2020 ; Sala et al., 2022 ; Shimizu & Negita, 2020 ; Torjesen, 2022 ; Uehara, 2020 ; Yamauchi et al., 2022 ; Yoneoka et al., 2021 ; Ko et al., 2022 ; Kato et al., 2022 ; Zeyu & Takikawa, 2021 ). An example of a user-friendly interface is presented in ( Dong et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the COVID-19 pandemic dynamics in Japan in the summer of 2020, 2021 and 2022 will be investigated in order to estimate the impact of vaccination levels on the numbers of new infections, death, and mortality rates. Some other studies of COVID-19 dynamics in Japan can be found in ( Chen et al., 2021 ; Fukumoto et al., 2021 ; Nesteruk, 2022a ; Nesteruk, 2022b ; Nesteruk, 2022c ; Niwa et al., 2020 ; Sala et al., 2022 ; Shimizu & Negita, 2020 ; Torjesen, 2022 ; Uehara, 2020 ; Yamauchi et al., 2022 ; Yoneoka et al., 2021 ; Ko et al., 2022 ; Kato et al., 2022 ; Zeyu & Takikawa, 2021 ). An example of a user-friendly interface is presented in ( Dong et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%